Exploring the Synergy of Physics-Based and IT Security Measures in ICS - Poposki, Filip; Babunski, Darko; Bogdanoski, Mitko; Zaev, Emil; Koleva, Radmila (IEEE, 2024)
With the rise of sophisticated cyber threats, safeguarding industrial control systems (ICSs) has become increasingly important. This paper delves into physics-based attack detection techniques within Cyber-Physical Systems (CPSs) and highlights their underutilization in Operational Technology (OT) and industrial automation, offering an analysis of current cybersecurity measures and frameworks. By integrating insights from both theoretical and practical perspectives, the study aims towards identifying the key challenges in modernizing legacy systems and stresses the importance of combining Information Technology (IT) with Operational Technology (OT) and emphasizes the importance of bridging the gap between Information Technology (IT) and OT security measures. The paper highlights the integration of physics-based detection methods, the research underscores their critical role in enhancing the security and resilience of ICSs. Conclusions stress the need for increased awareness and adoption of these techniques within OT environments.
Keywords: Industrial Control Systems; Cyber-physical Systems; Cyber-physical Attacks; Attack Detection; Kalman Filter